Neuromonitoring and follow-up in patients with congenital heart disease in Spain - Alexandra Belfi; Laia Vega; Marta Aguar; María Carmen Bravo; Débora Cañizo; Laura Díaz Rueda; Marta Camprubí-Camprubí; Alexandra Belfi; Laia Vega; Marta Aguar; María Carmen Bravo; Débora Cañizo; et al. (Anales de Pediatría (English Edition))
Introduction: There is evidence of the high incidence of neurological abnormalities in patients with congenital heart disease (CHD). Despite this, perioperative neuromonitoring strategies and long-term follow-up protocols are not standardized in Spain. Objective: The aim of our study was to describe current clinical practice in neuromonitoring, neuroimaging and neurodevelopmental follow-up in patients with CHD in Spanish hospitals that perform paediatric cardiac surgery (PCS). Material and method: We conducted a survey by adapting a questionnaire originally developed by the European Association Brain and Congenital Heart Disease Consortium to collect data on aspects such as the implementation of perioperative neuromonitoring and the type of neuroimaging techniques and neurological follow-up performed. The questionnaire was distributed to the 19 Spanish hospitals that perform PCS. Results: We received responses from 17 centres. Eighty-eight percent performed some type of preoperative neuroimaging and 81% postoperative monitoring. The most widely used technique was transfontanellar sonography. Fifty-six percent of the centres used some form of intraoperative neuromonitoring, most frequently near-infrared spectroscopy. Nineteen percent had an established protocol for the follow-up of these patients and 13% were in the process of developing it. Conclusions: There is considerable heterogeneity in neuromonitoring, neuroimaging and neurologic follow-up practices in the management of patients with CHD in hospitals that perform PCS in Spain. These findings highlight the need to pursue a consensus in order to standardise neuromonitoring and neurologic follow-up strategies in children with CHD in Spain. Resumen: Introducción: Existe evidencia de la alta incidencia de alteraciones neurológicas en pacientes con cardiopatía congénita (CC). No obstante, en España, las estrategias de neuromonitorización perioperatorias, así como los protocolos de seguimiento no estan estandarizadas. Objetivo: El objetivo de este estudio es describir las prácticas clínicas actuales en cuanto a neuromonitorización, neuroimagen y seguimiento del neurodesarrollo en pacientes con CC en los hospitales españoles que realizan cirugía cardíaca pediátrica (CCP). Material y método: Se diseñó una encuesta adaptando un cuestionario previamente desarrollado por The European Association Brain and Congenital Heart Disease Consortium, en la que se exploraron aspectos relacionados con la neuromonitorización peri-cirugía, las técnicas de neuroimagen y el seguimiento neurológico. La encuesta se envió a los 19 hospitales españoles con programa de CCP. Resultados: De los hospitales contactados, se obtuvo respuesta de 17. El 88% de los centros realiza algún tipo de neuroimagen pre-cirugia y un 81% post-cirugía. La ecografía transfontanelar es la técnica más utilizada. El 56% de los centros utiliza alguna estrategia de neuromonitorización intraquirúrgica, siendo la espectroscopia de infrarrojo cercano la más utilizada. Solo el 19% de los centros disponen de un protocolo de seguimiento para estos pacientes y el 13% están en proceso de planificación. Conclusiones: Existe una gran heterogeneidad en las prácticas de neuromonitorización, neuroimagen y seguimiento neurológico para pacientes con CC en los centros españoles con CCP. Estos hallazgos subrayan la necesidad de avanzar hacia un consenso que permita estandarizar las estrategias de neuromonitorización y seguimiento neurológico en niños afectos de CC en España.